1998
DOI: 10.1159/000017067
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Ceruloplasmin and Superoxide Dismutase in Patients with Alzheimer’s Disease

Abstract: The copper-containing enzyme superoxide dismutase (SOD) is a key enzyme in suppressing the amounts of superoxide anion radicals. Ceruloplasmin, the copper-transporting protein in plasma, also possesses an important redox capacity. In this study the levels of copper and ceruloplasmin as well as SOD-activity and ceruloplasmin oxidative activity were analyzed in order to throw some light on possible defects in copper mechanisms in patients diagnosed with Alzheimer’s disease (AD). The study included 44 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
2
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 10 publications
(10 reference statements)
7
41
2
6
Order By: Relevance
“…The activity of SOD in erythrocytes was also found significantly lower while the amounts of copper in plasma and of ceruloplasmin in serum were the same in both groups (Snaedal et al 1998). The results therefore indicated that a kind of copper dyshomeostasis prevailed in Alzheimer's disease since the synthesis of the enzyme proteins or the mechanism of incorporation of the copper atoms into the molecules, or both, were defective.…”
mentioning
confidence: 76%
“…The activity of SOD in erythrocytes was also found significantly lower while the amounts of copper in plasma and of ceruloplasmin in serum were the same in both groups (Snaedal et al 1998). The results therefore indicated that a kind of copper dyshomeostasis prevailed in Alzheimer's disease since the synthesis of the enzyme proteins or the mechanism of incorporation of the copper atoms into the molecules, or both, were defective.…”
mentioning
confidence: 76%
“…5 In fact, even those authors reporting decreased levels in AD of absolute serum copper confirm a copper/ceruloplasmin dyshomeostasis. 10,11,17,18 Snaedal et al, (1998) 11 found similar levels of absolute serum copper in AD and controls, but significantly lower concentrations of ceruloplasmin, which corresponds to a higher concentration of 'free' copper in AD than in controls. Kessler and colleagues (2006) 17 reported data coherent with a 2.5 fold increase of 'free' copper in AD with respect to normal values (<1.6 μmol/L).…”
Section: Introductionmentioning
confidence: 85%
“…There is new evidence suggesting that brain copper may redistribute outside the neuronal cell, leaving it relatively deficient. 7 Although past studies in man have found no differences between AD and controls in serum copper levels, [8][9][10][11] more sophisticated measurements have recently shown both an increase, [12][13][14][15] and a decrease of these levels, 16,17 thus opening a debate on a toxic or protective role of copper in AD. Results from our laboratory, though, suggest that it is the ceruloplasmin-copper relationship, rather than the level of absolute (i.e., bound and not bound to ceruloplasmin) serum copper, that may be the key issue in interpreting in vivo copper findings in AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper concentration in plasma on the other hand was in both studies within normal limits in patient groups and the controls. It was therefore concluded that a kind of copper dyshomeostasis prevailed in these degenerative diseases of the central nervous system since the synthesis of the enzyme proteins or the mechanism of incorporation of the copper atoms into the molecules, or both, were defective (Snaedal et al 1998, Tó rsdó ttir et al 1999). The present results extend these studies to include the third neurodegenerative disease, amyotrophic lateral sclerosis.…”
mentioning
confidence: 99%